Implementasi Pembelajaran Berdiferensiasi dengan Station Rotation untuk Meningkatkan Kemandirian Belajar melalui Materi Sistem Tata Surya pada Siswa Kelas 8 SLB B YAAT Klaten - Ayu Asti Firdaus; Indriyani Indriyani; Tety Seftiyana; Subagyo Subagyo; Isna Fauziah (Universitas Sebelas Maret, 2025)
This study aims to improve learning independence among eighth-grade deaf students at SLB B YAAT Klaten through the implementation of differentiated instruction using the station rotation model in the solar system topic. The research employed a Classroom Action Research (CAR) approach conducted in two cycles. The subjects were nine students with diverse learning needs and characteristics. Data were collected through observation, interviews, and documentation. The findings indicate that the station rotation strategy effectively encourages students to become more independent in completing tasks, managing their time, and initiating learning activities. This model has proven to be effective in accommodating individual learning needs and fostering an inclusive classroom environment. In conclusion, differentiated instruction through station rotation plays a significant role in enhancing the learning independence of students with special needs